Fungsi Badan Pengawas Keuangan dan Pembangunan dalam Melakukan Perhitungan Kerugian Keuangan Negara pada Perkara Tindak Pidana Korupsi - Kadek Teguh Aryasa; I Made Minggu Widyantara; Luh Putu Suryani (Warmadewa Press, 2021)
State financial losses are an important issue to study. Corruption in Indonesia is a major problem so far it has never been resolved, starting from the central government to the regions. This has had a bad effect on the Indonesian economy. In practice, the Investigating Prosecutor at the Denpasar District Attorney often conducts investigations in the framework of calculating state financial losses. This study aims to determine the legality of the results of investigative audits issued by the Financial Supervisory Agency as evidence in proving state financial losses in corruption cases and to determine the factors that influence the Investigative Prosecutor to more frequently ask Financial Supervisory Agency for assistance to conduct investigative audits. The research method used is empirical legal research with a qualitative approach and a descriptive approach. The data sources are primary data obtained directly from the Denpasar District Attorney with interview techniques and secondary data from legal theories. The results show that the results of the investigative audit conducted by the Financial Supervisory Agency can be used as evidence at trial because their validity meets the elements contained in Article 184 of the Criminal Procedure Code and the tendency of the Investigative Prosecutor at the Denpasar District Attorney to conduct an investigative audit of the Financial and Development Supervisory Agency efficiency and effectiveness policy factors as well as human resource factors.